БАЗАР ЭКОНОМИКАСЫНА ӨТИЎ ДӘЎИРИНДЕ ҚАРАҚАЛПАҚСТАН САНААТЫНДА ЭКОНОМИКАЛЫҚ ӨЗГЕРИСЛЕР - Сарыбаев, А.К. (SCIENCE and SOCIETY, 2024)
This article shows the difficult economic situation of industrial factories of the Republic of Karakalpakstan during the transition to a market economy. The processes of economic transformation of the industrial sector of the region in the 90s of the twentieth century are also reflected on the path of economic reforms.
Keywords: market economy; economic situation; economic reform; privatization of state property; reforms in industry